Pendampingan Peran Orang Tua dan Perkembangan Bahasa Anak Usia Dini di Kampung Sindangsari - Sari, Dita Kumala (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The aim of this community service is to provide knowledge about the role of parents and children's language development. Socialization assistance activities are carried out through the preparation stage, implementation stage, program evaluation stage and reporting stage. The targets of this service are parents or guardians of TKA/TPA/DTA Bustanul Ulum students. The result of this service is that there are several roles of parents that can support early childhood language development, including (a) introducing good and correct greetings in the family, (b) practicing the pronunciation of short or simple sentences when receiving, requesting and asking questions. to other people, (c) inviting children to recognize objects around them, (d) inviting children to talk, (e) reading stories or fairy tales, and (f) implementing a democratic parenting style.